IMPACT OF INSTITUTIONAL QUALITY ON THE ECONOMIC GROWTH OF PAKISTAN - Sadaf Jameel; Dr. Balach Rasheed; Dr Parvez Ahmed Shaikh (Policy Research Journal, 2025)
Purpose: This study was directed to present how the quality of institutions impacts economic growth. This study was specially conducted to check the relationship between institutional quality and the economic growth of Pakistan. Methodology: This study used the data from the period 1996 to 2020. The study used control of corruption and government expenditure as explainer variables and GDP growth as economic growth. The study used an auto-regressive distributed lag model to find the results. Final findings: The final findings of the paper are control of corruption had no impact on economic growth, and government expenditure was positively related to economic growth and higher impact on economic growth in Pakistan. Originality/ Value: This study shed light on earlier uncleared studies about the relationship between the quality of institutions and economic growth. This study also explained the quality of institutions and economic growth of Pakistan. Paper Type: Research Paper